1993
DOI: 10.1002/app.1993.070471217
|View full text |Cite
|
Sign up to set email alerts
|

Selection of elastomeric membranes for the removal of volatile organics from water

Abstract: SYNOPSISA wide range of homogeneous elastomeric membranes has been prepared using dicumylperoxide as a general cross-linking agent. The membranes have been used for both equilibrium sorption measurements and steady-state pervaporation experiments to study solution-diffusion phenomena in the removal of volatile organic components from aqueous solutions. Pervaporation experiments have been performed under identical hydrodynamic conditions in order to fix the boundary layer mass transfer coefficient a t a constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…Two previous studies on silicones [25,57] obtained a value of ı p = 15.3 MPa 1/2 , while three other studies [10,34,53], suggested using ı p = 15.8, 16.2 and 15.1 MPa 1/2 , respectively.…”
Section: Liquidmentioning
confidence: 97%
See 1 more Smart Citation
“…Two previous studies on silicones [25,57] obtained a value of ı p = 15.3 MPa 1/2 , while three other studies [10,34,53], suggested using ı p = 15.8, 16.2 and 15.1 MPa 1/2 , respectively.…”
Section: Liquidmentioning
confidence: 97%
“…Eq. (2) arises directly from the definition of , where l is the density of the liquid, and has been published previously [31][32][33][34]. All calculations of from are based on the Flory-Rehner theory [8], which states that the change in the Gibbs function on mixing a liquid with a polymer, of density , is given by…”
Section: Theorymentioning
confidence: 99%
“…The degree of sorption for BT-DA-SIDA prepared by the two-pot system tends to increase with the hydrophobicity of organic compounds, and the degree of sorption of TCE is found to be the highest (about 1800 wt %). In Figure 4, the degree of sorption for the crosslinked PDMS membranes [25][26][27][28] is also shown, and compared with that of BTDA-SIDA prepared by the two-pot system. The degree of sorption for the crosslinked PDMS membranes increases gradually with the hydrophobicity of the organic compounds.…”
Section: Sorption and Sorption Selectivitymentioning
confidence: 99%
“…Elastomeric organophilic membranes that preferentially permeate organic compounds but retain water are widely used to remove organic compounds from water. Nijhuis et al 5 have prepared a wide range of homogeneous elastomeric membranes, such as nitrilbutadiene rubber (NBR), ethylene-propylene terpolymer (EPDM), and poly(dimethylsiloxane) (PDMS), which showed extremely high pervaporation. In selecting membrane material according to the solution diffusion mechanism by which the pervaporation process is most expressed, physicalchemical interactions with permeating molecules should be taken into account in terms of their solubilities and diffusivities in the membrane material.…”
Section: Introductionmentioning
confidence: 99%